Ethnomathematics in Islamic Local Wisdom - Malik, Fatus Atho’ul; Wanto, Wanto; Amalliyah, Nor (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study explores ethnomathematics in Islamic local wisdom in Kemantren Village, Lamongan Regency, focusing on Islamic traditions surrounding the tomb of Maulana Ishaq. Using qualitative descriptive methods through observation and literature review, this study examines mathematical elements embedded in the architecture of Maulana Ishaq's tomb, Al-Abror Mosque, heritage sites, and the Islamic cultural practices that have developed in the village. Data were collected through interviews, observations, and literature analysis involving ten participants, including religious figures, mathematics teachers, tomb caretakers, and local residents. The research findings reveal that the Muslim community in Kemantren has preserved advanced mathematical understanding through religious and cultural traditions, particularly in the context of Islamic rituals and local religious practices. This study provides an integrative framework for embedding Islamic cultural ethnomathematics into mathematics pedagogy and cultural heritage preservation.